Psychometric Properties of Sinhala Version of Short-Form McGill Pain Questionnaire-2 (SF MPQ-2-Sin) among Patients with Cancer Pain in Sri Lanka - Nirosha P. Edirisinghe; Thamasi R. Makuloluwa; Thamara D. Amarasekara; Christine S. E. Goonewardena (Pain Research and Management)
Introduction. Pain is one of the most common and unpleasant symptoms that distress the well-being of patients with cancer. Considerable evidence supports the validity and reliability of the McGill Pain Questionnaire (MPQ) and its short forms, the SF MPQ and SF MPQ-2—which are the most widely used tools for pain assessment—in terms of patients with cancer. Pain and its characteristics are best assessed using validated and culturally adapted tools developed in participants’ mother tongue. Although many pain assessment tools are available worldwide, only a limited number of them have been translated into Sinhala language and validated in Sri Lanka. We aimed to translate SF MPQ-2 into Sinhala language and validate using Sinhala-speaking patients suffering from cancer pains in Sri Lanka. Materials and Methods. Translation has been conducted according to the guidelines laid down by Mapi Research Trust, in five stages, namely, forward translation, backward translation, expert opinion, cognitive debriefing interviews, and proofreading. The questionnaire was administered among 207 patients attending Apeksha Hospital, Sri Lanka, who are suffering from cancer pain. Content validity was tested using expert opinion, and face validity, by interviewing patients with cancer pain. Factor structure was tested through a factor analysis, and reliability, by internal consistency with Cronbach’s alpha. Results. A total of 207 participants (112 males and 95 females), aged between 20 and 80 years, were included in the study. Factor analysis identified four factors compatible with studies done in other countries, which explained 53.5% of the variance. The analysis of data indicated Cronbach’s alpha of neuropathic, affective, intermittent, and continuous subscales as 0.768, 0.791, 0.824, and 0.789, respectively, which were over the acceptable threshold of 0.70. Confirmatory factor analysis supported the four-factor model. Conclusion. SF MPQ-2-Sinhala version is a statistically proven reliable and valid pain descriptor which can be utilized to evaluate pain suffered by patients with cancer in Sri Lanka whose mother tongue is Sinhala.